Гальванические токи у людей с металлическими имплантатами в теле в сочетании с металлическими зубопротезными конструкциями (Эндодонтия Today)
Regarding cases there is an intolerance metal implants. For the majority of such patients are available metal orthopedic materials. These patients have streams of high galvanic currents between implants and metal dental orthopedic in a mouth. Removal orthopedic metals leads to disappearance of streams of high galvanic currents with disappearance of pathological symptoms гальванизма. Allergy metals implants and orthopedic materials in this case plays a supporting role.